El método multisensorial como estrategia psicopedagógica para reforzar la lectoescritura en estudiantes de segundo grado de la Escuela de Educación Básica Alonso de Mercadillo, 2021-2022 - Solano Villalta, Carmen Rocío (2023)
The present curricular integration work had the general objective of implementing the multisensory method as a psycho-pedagogical strategy to reinforce literacy in second grade students of the Alonso de Mercadillo School of Basic Education 2021-2022. The research had a qualitative-quantitative approach, descriptive type, pre-experimental design, cross-sectional, scientific, inductive, deductive, analytical, synthetic, and statistical methods were used; The techniques of the interview, observation, achievement sheet, and the Literacy Analysis Test (T.A.L.E) were used, applied to a sample of 29 students. From the obtained result; from the interview with the teacher, he mentions that he currently uses strategies to reinforce literacy; from the results of the observation in the class, the use of strategies for the teaching of reading and writing is not evident; Regarding the level of literacy, in reading the students reach the level below the minimum: reading of letters (62%), reading of syllables (45%), reading of words (55%), reading of texts (72% ), and reading comprehension (83%); Likewise, in writing they reach a level below the minimum: dictation (62%) and spontaneous writing (76%), due to the high number of errors they make in the test. It is concluded that the teacher does not use strategies to reinforce literacy; the reading and writing level of the students is below the minimum. For this reason, the proposal for psycho-pedagogical intervention was designed and implemented through a guide of multisensory activities; making significant progress; considering positive the guide to reinforce reading and writing in students. Keywords: Multisensory method, teaching-learning, psycho-pedagogical proposal, literacy, multisensory activities.